2014
DOI: 10.1371/journal.pone.0088844
|View full text |Cite
|
Sign up to set email alerts
|

Is Transcriptomic Regulation of Berry Development More Important at Night than During the Day?

Abstract: Diurnal changes in gene expression occur in all living organisms and have been studied on model plants such as Arabidopsis thaliana. To our knowledge the impact of the nycthemeral cycle on the genetic program of fleshly fruit development has been hitherto overlooked. In order to circumvent environmental changes throughout fruit development, young and ripening berries were sampled simultaneously on continuously flowering microvines acclimated to controlled circadian light and temperature changes. Gene expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 160 publications
(197 reference statements)
3
45
0
Order By: Relevance
“…Of all the phenylpropanoid metabolites, quercetin aglycon was the only one found to increase along the day, suggesting its potential role as a carbon pool for the biosynthesis of flavonoids, readily used upon the nocturnal replenishment of carbohydrates. This agrees with recent evidence showing that phenylpropanoid-related gene expression is largely regulated during the night in ripening grape berries (Rienth et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Of all the phenylpropanoid metabolites, quercetin aglycon was the only one found to increase along the day, suggesting its potential role as a carbon pool for the biosynthesis of flavonoids, readily used upon the nocturnal replenishment of carbohydrates. This agrees with recent evidence showing that phenylpropanoid-related gene expression is largely regulated during the night in ripening grape berries (Rienth et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…The latter exhibited temporal trends that were less pronounced during cloudy days and, in the absence of relevant data, were attributed to differences in leaf photosynthesis. In addition, grape transcriptome was recently found to differ between day and night (Rienth et al, 2014), and exhibit circadian patterns (Carbonell-Bejerano et al, 2014). That said, although season-long trials show a strong association between grape gene expression patterns and metabolite accumulation (Degu et al, 2014;Deluc et al, 2007;Matus et al, 2009), in a short-term diurnal trial in potato, transcripts and the metabolite profile of leaves were poorly correlated (Urbanczyk-Wochniak et al, 2005).…”
mentioning
confidence: 99%
“…Proteomics studies also reported an increase in ROS scavenging enzymes toward ripening (Giribaldi et al, 2007;Negri et al, 2008). The subject remained wrapped in controversy because other authors did not obtain the same results (Terrier et al, 2005), until Rienth et al (2014) shed some light onto what might be causing such disparity of results. The authors, in yet another transcriptomic assay of grape berries, found that the oxidative burst occurs markedly during the night, at ripening, following the same trend as sugar transport and phytoalexin synthesis.…”
Section: Oxidative Burstmentioning
confidence: 99%
“…Although a certain number of publications have reported the results of transcriptome analyses in grape, most used EST-based microarrays and their data did not cover the whole grape genes. After the update of the grape genome data by Grimplet et al (2012), transcriptome analysis using a microarray covering the whole grape genes became popular (Pastore et al, 2011(Pastore et al, , 2013Fasoli et al, 2012;Gambino et al, 2012;Lijavetzky et al, 2012;Young et al, 2012;Dal Santo et al, 2013;Carbonell-Bejerano et al, 2014aDai et al, 2014;Rienth et al, 2014aRienth et al, , 2014b. Recently, RNA sequencing has also become popular in the transcriptome analysis of grape Fasoli et al, 2012;Perazzolli et al, 2012;Sweetman et al, 2012;Venturini et al, 2013;Chitwood et al, 2014;Li et al, 2014;Vitulo et al, 2014;Xu et al, 2014).…”
Section: Omics-based Studies In Grapementioning
confidence: 99%